Qualidade física do solo em sistemas de produção no Mato Grosso - Anghinoni, Guilherme (2016)
Brazilian agriculture receives great contribution of the Midwest region of Brazil, which is under the cerrado biome and responsible for much of the Brazilian production of grains and cotton fiber. On the other hand, crop yields have shown stagnation, which may indicate a problem related to the inappropriate use of some technologies. Despite the fact that soil physical quality (SPQ) is important to the quality of an agricultural production system, its study is not yet widespread, especially in the Cerrado production systems. This study tested the hypothesis that the physical quality of a dystrophic Latossolo Vermelho, located in the Midwest of Brazil, is influenced by soil tillage systems and production systems with use of succession or crop rotation. We determined soil physical properties in no tillage (NT) and conventional tillage (CT), at the 0.0-0.1 m, 0.1-0.2 and 0.2-0.4 m layers of an Oxisol under 5 different production systems composed of cotton crop succession and rotation strategies in Itiquira-MT. The experimental design is a randomized block with 4 replications and split plots. We measured soil Air permeability (Ka), Pores continuity index (K1),Moisture at field capacity (FC), porosity at the macropores domain (PORm) , porosity at the soil matrix domain(PORs), soil air capacity (CASOLO), air capacity of the soil matrix (CAMAT), the relationship between moisture at FC and total porosity (FC/TP ), Bulk density (BD) as well as the yield of cotton and soybean crops. The NT 0-0.1 m layer had higher BD and FC than the CT. Differently, the CT had greater macroporosity, gaseous conductivity and better continuity of pores. The production systems of cotton monoculture and cotton/millet succession showed lower values of PORm. At the 0-0.2 m layer, PORs was greater under PC in the production systems that included the soybean crop. The 0.2-0.4 m layer of CT had higher FC and POMAT, while K1 was lower. The NT resulted in 10.2% higher soybean yield than the one found for PC, attributed to the better water supply to the crop under NT. The cotton yield of fiber and seeds was lower in the cotton monoculture, although it is not possible to link this result to SPQ differences between the production systems. We conclude that the different cultivation schemes and tillage systems affected the soil physical quality. However, the effect of soil physical quality in crop yields was only observed when the plants were subjected to water deficit, as in the case of the soybean crop.